Kaempferol, a dietary flavonoid, ameliorates acute inflammatory and nociceptive symptoms in gastritis, pancreatitis, and abdominal pain. Issue 7 (5th June 2015) - Kim, Shi Hyoung; Park, Jae Gwang; Sung, Gi‐Ho; Yang, Sungjae; Yang, Woo Seok; Kim, Eunji; Kim, Jun Ho; Ha, Van Thai; Kim, Han Gyung; Yi, Young‐Su; Kim, Ji Hye; Baek, Kwang‐Soo; et al.
<x xml:space="preserve">Abstract</x> Kaempferol (KF) is the most abundant polyphenol in tea, fruits, vegetables, and beans. However, little is known about its in vivo anti‐inflammatory efficacy and mechanisms of action. To study these, several acute mouse inflammatory and nociceptive models, including gastritis, pancreatitis, and abdominal pain were employed. Kaempferol was shown to attenuate the expansion of inflammatory lesions seen in ethanol (EtOH)/HCl‐ and aspirin‐induced gastritis, LPS/caerulein (CA) triggered pancreatitis, and acetic acid‐induced writhing.